The Influence of Chemical Composition on Cobalt-Based Alloys - Mirabela Georgiana MINCIUNA; Petrică VIZUREANU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
Cobalt-based alloys contain up to 50% cobalt, which means that they provide the material with increased abrasion resistance at high temperatures. Cobalt is similar to nickel because it is a hard material that is very resistant to wear and corrosion, especially at high temperatures. It is generally used as an element in alloys, due to its resistance to corrosion, but also due to its magnetic properties. In all cases, the introduction of an implant into an organism is likely to induce chemical, mechanical, electrical, thermal, magnetic and atomic interactions.